Phenomenology Study: Nurses' Experiences in Care of Covid-19 Patients in the Intensive Care Unit of the Covid-19 Emergency Hospital Wisma Athlet Jakarta Pusat - Wasis Widodo; Tria Astika Endah Permatasari; Diana Irawati (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
The Covid-19 outbreak is currently a global pandemic all over the world. Nurses are jobs that are most often exposed to disease and infection. The Covid-19 outbreak has made nurses experience changes in their work and lives. Objectives to Identifying the experience of nurses in treating Covid-19 patients in the ICU. This study uses a qualitative research design with a phenomenological approach. Data was collected by telephone interview and analyzed by thematic analysis method. Participants in this study amounted to 12 people who were selected by purposive sampling technique. The data obtained were analyzed using the Colaizzi approach. The results of the research analysis found 5 themes, namely: Experience while working to treat patients with COVID-19 in the Intensive Care Unit, Changes experienced in both positive and negative terms, Problems that occur related to the resources encountered, Constraints faced and how to overcome them and Expectations of nurses working in the Intensive Care Unit. The results showed that nurses while caring for Covid-19 patients in the ICU were still faced with various obstacles. For this reason, social support, spiritual and spiritual guidance and training regarding Covid-19 are needed.